2017
DOI: 10.5430/jnep.v8n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with gerontological career choice: The role of curriculum type and students’ attitudes

Abstract: Background and objective: Caring for a growing aging population presents a challenge in contemporary health care. This study aims to identify factors associated with nursing student's career choice in older adult care and predictors of attitudes toward older adults. Such information is critical to inform effective gerontological nursing education. Methods: Undergraduate nursing students (N = 411) from three nursing schools in California participated in a cross-sectional, web-based survey. Results: In covariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In the same stream, higher percentage was reported by Faronbi et al [6] in Ile-Ife, Nigeria who find out that more than two third of participants held a positive attitude towards the care of elderly. Also, Lee et al [18] and Lee et al [19] in USA stated that nursing students expressed more positive than negative attitude toward elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In the same stream, higher percentage was reported by Faronbi et al [6] in Ile-Ife, Nigeria who find out that more than two third of participants held a positive attitude towards the care of elderly. Also, Lee et al [18] and Lee et al [19] in USA stated that nursing students expressed more positive than negative attitude toward elderly.…”
Section: Discussionmentioning
confidence: 99%
“…A positive association between attitudes and work preferences with older people was reported in some studies. 13,14,[21][22][23] However, several studies have reported that there was no significant association between attitudes and work preferences toward older people. 24,25 It was reported that although nursing students have a positive attitude toward older people, they are not interested in aged care.…”
Section: Attitudes and Work Preferences Toward Older People Among 199mentioning
confidence: 99%
“…Various measures, such as public image campaigns and improving working conditions, have been taken to increase retention and students’ interest in long-term care (LTC) of older adults ( OECD, 2020b ). Studies have also shown that formal education in gerontology, combined with personal encounters with older people, has positive implications for how older adults are regarded and treated by younger generations and health care professionals ( Lee et al, 2018 ; Mattos et al, 2015 ; Mattsson & Pietilä Rosendahl, 2017 ). Much of the focus has been on student and nurse perspectives, while this study explores nurse educators’ conceptions of GN in two different cultures, with similar challenges in increasing nursing students’ interest and competency in LTC of older adults with compromised health.…”
Section: Introductionmentioning
confidence: 99%